Strengthening Indonesia’s sustainable palm oil policy: Addressing climate change and enhancing global market integration - Pasaribu, Anggi Prabawa (Journal of Sustainability, Society, and Eco-Welfare, 2025)
Background: This study investigates the strengthening of sustainable palm oil plantation policies in Indonesia as a strategic response to global climate change challenges and growing international market pressures. The study emphasizes the importance of simplifying certification processes, strengthening local institutional capacity, and promoting participatory governance. Multi-stakeholder collaboration, technological support, and policy adaptation to local contexts are identified as critical enablers of an inclusive and effective sustainability framework. Methods: Using a qualitative approach through in-depth interviews with diverse stakeholder government officials, smallholder farmers, corporations, NGOs, and academics the research uncovers the varying perceptions, capacities, and experiences that shape the current sustainability landscape. Findings: The findings reveal a significant disconnect between policy formulation and field-level implementation, especially among smallholders who face barriers such as inadequate access to information, technology, and finance. Certification schemes like ISPO and RSPO, while central to sustainability efforts, are often perceived by smallholders as complex and costly. Additionally, limited supervisory capacity, inconsistent intergovernmental coordination, and unresolved land conflicts further impede policy effectiveness. Importantly, the findings underscore the need to enhance transparency across the supply chain and foster innovation through public-private-academic partnerships. Increased investment in smallholder training, digital monitoring systems, and conflict resolution mechanisms is vital to closing the gap between policy and practice. Conclusion: Ultimately, this research highlights the need for an integrated policy approach that harmonizes regulations, empowers smallholders, enhances transparency, and supports innovation paving the way for a resilient and competitive palm oil industry that contributes to both national development and global climate goals. Novelty/Originality of this article: This study offers a novel contribution by bridging the gap between sustainability policy formulation and field-level implementation in Indonesia’s palm oil sector, with a particular focus on smallholder realities.